NOVOS TEMPOS SAÚDE MENTAL, CAPS E CIDADANIA NO DISCURO DE USUÁRIOS E FAMILIARES - Cirilo, Lívia Sales (2006)
The madness has been observed form different ways along the history. If, during the Antiquate madness had been conceded as a divine manifestation, in the Medieval Age as a result of demoniac positions, in the eighteenth century it gains the status of a mental disease, starting to demand segregationist mechanisms and treatment excluding, coming to a head with the emergency of the Second Great War we can observe some pronouncements that tries to reform the dominating habits and offer a new view over the mental disturbance healing. In this context the Italian Democratic Psychology stands out, which has influenced in on a definitive way the Brazilian Psychology Reformation. In Brazil the pronouncement that aims at the optimization of the attendance on mental health starts from the seventies on, when we find out the emergency of several substitutive services such as CAPS and other devices like therapeutic shelters, the going back home programs and others, which goals are to provide the independency and the citizenship s ransoms of the mental sick porter. In Campina Grande city the pronouncement over the Psychiatric Reformation has acquired emphasis form the Federal Interference declared in one of the psychiatric hospitals from the city, coming to a head with it s own discredit from the SUS*- Unit Health System , on it s closure and fortifying of a substitutive net of Mental Health. In this work, a study about the conceptions of the usuries and their family is made, it is about concepts such as citizenship, mental health, and detaching some of the subjects like the family s participation, offered attendance on CAPS, characterization of the psychiatric hospitals and the stigma and misconception that rounds a mental illness. Fifteen usuries and fifteen relatives had been interviewed for this research; they are from a CAP in Campina Grande city. The results of the interview, which had been made up from a half-constructed interview regulation, had been taped and transcript integrally, and analyzed based on the presupposed of Social Discursive Psychology. About the discussions over the results, we can evidence that, among the explanations given by the interviewed persons about the mental disturbance causes biological, psychosocial, socioeconomic and psychological are detaching. By the time we conceived the mental disturbance it had been standing out, on the speech of the interviewed persons the description about the disease s symptomatology and it s situations on the crises. The meaning of the familiar participation has also been mentioned by the interviewed persons to evaluate the rules of functioning from the CAPS, which demands the participation in the family s group. The narration of the interviewed about the attendance of the CAPS were extremely important, as well as theirs characterizations about the treatment offered in the psychiatric hospital, where most of the exhibit of the CAPS had a positive evaluation about the performance and points such as excessive medication and familiar isolation had been mentioned about the psychiatric placement. Relating the citizenship that great part of the interviewed think that concept is joint to acquirement of documents and voting, accentuating, right away, the conception of citizenship attached to fellowship acts and helping the needed, to the right of being attended on a health service, where the speeches that deal with misconception and stigma had been standing out, which the carriers of mental disturbance are victims.